ENTREPRENEURSHIP-BASED CURRICULUM DEVELOPMENT STRATEGY IN MADRASAH ALIYAH IN FACING GLOBAL CHALLENGES - Mustaqim Mustaqim; Muhammad Husain (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to formulate an adaptive entrepreneurship-based curriculum development strategy to provide a strategic roadmap for transforming Madrasah Aliyah into an innovation center in the face of global challenges and digital economic disruption. The method used is a descriptive qualitative approach with data collection techniques through triangulation, combining participant observation, in-depth interviews with key informants (Headmaster, Vice Head of Curriculum, teachers, and students), and documentation studies. The results show that the curriculum development strategy is carried out through the integration of Islamic "Technopreneurship," which combines digital literacy with sharia business ethics, and the implementation of a cross-disciplinary Project-Based Learning (PjBL) approach. The utilization of modern infrastructure, such as virtual business laboratories and internal madrasah marketplaces, has proven effective in bridging the gap between theory and practice while reducing students' managerial risks. Furthermore, strategic collaboration through the "Triple Helix" model involving synergy between madrasah, industry, and government ensures that teaching materials remain relevant to global market dynamics. The contribution of this research lies in providing a holistic curriculum development model that not only creates financial independence and economic agility for graduates but also maintains moral integrity through the character of akhlakul karimah as a primary foundation in the digital era.